Analisis Pengelolaan Trias Usaha Kesehatan Sekolah (UKS) di Tingkat SMP Se-Kota Bandar Lampung (Studi Kualitatif) - Nana Novariana; Nur Sefa Arief Hermawan (Jurnal Kesehatan, 2018)
School Health Effort Programs held at all levels of education. The purpose of School Health Efforts was to improve the quality of education and learning achievement of learners by improving the behavior of clean and healthy life and health status and create a healthy environment, thus allowing harmonious growth and optimum development in the framework of human formation in Indonesia as a whole. The purpose of this research was to analyze more deeply about the management of Trias School Health Efforts (UKS) at Junior High School level in Bandar Lampung City in 2017. This research was a qualitative research type with descriptive analysis research design with phenomenology approach. The study was conducted from March to April 2017 at the Junior High School level in Bandar Lampung city, the Office of the Ministry of Religious Affairs of Bandar Lampung City, the Bandar Lampung City Health Office, and the Education Office of Bandar Lampung City. With informants, 31 informants from headmasters, UKS teachers, and UKS officers, and staff organizing UKS at Health Office, Education Office, and Ministry of Religious Affairs. The conclusion of the research result was that in general tries of UKS in junior high school level as Bandar Lampung City has been running quite well, both in terms of health education, health service, and healthy environment coaching. It was just that in each of the triads still need more and more coaching. As well as from the Community Health Centres can further channel the new sciences that have been obtained for more fostering schools that exist within the target area.